Plato at Syracuse Essays on Plato in Western Greece with a new translation of the Seventh Letter by Jonah Radding - Reid, Heather L. (Parnassos Press - Fonte Aretusa, 2019)
This book is born from a desire to understand how Plato influenced and was influenced by the intellectual culture of Western Greece, the ancient Hellenic cities of Sicily and Southern Italy. In 2018, a seminar on Plato at Syracuse was organized, in which a small group of scholars discussed a new translation of the Seventh Letter and several essays on the topic. The seminar was intense but friendly, having attracted a diverse group of scholars that ranged from graduate students to senior professors, hailing from at least three different continents, and representing a variety of academic specialties. We tried to create a book that would invite further study of the topic by identifying new questions to be asked while addressing enduring issues. The essays consider the historical, political, and philosophical implications of Plato's involvement in Syracuse. They also look at the reception of his voyage among fellow philosophers, ancient and modern. Readers may come to their own conclusions, but one thing is clear: the history of philosophy was profoundly influenced by Plato's voyages in Western Greece.